Tri Pusat Pendidikan Dalam Pengembangan Pendidikan Islam Di Indonesia - Fherlia Fherlia; Alimni Alimni (Al-Khair Journal : Management, Education, and Law, 2023)
Abstract: Tri education centers in Indonesia are still difficult to develop, characterized by difficulties in integrating educational programs between families, schools and communities who are responsible for education. The purpose of this research is to map and analyze the tricenter of education in the development of education in Indonesia. Using the library or literature study method, the data sources are obtained from reviews of scientific writings, scientific articles, scientific books both online and in print. The results of the study can be concluded that the education tricenter consists of family, school and community education. Family education is the first educational institution, because parents always prepare good educational supplies for their children. Then school education is that children get education through the school environment, humans receive formal education through educational and extracurricular materials with all the provisions and structures that have been regulated therein, formal education in this school is taken for nine years normally arranged through elementary, junior high, and high school programs. and high school. Meanwhile, community education is through non-formal educational institutions, such as tutoring (tutoring), TPQ (Quran Education Park), community organizations (Mosque Islamic Youth), and many other non-formal educational institutions in society. Thus it can be suggested that in an effort to develop education, then increase the role of functions and responsibilities of the tricenter of education in Indonesia.Keywords: Three Education Centers, Development, Islamic Education.Â Abstrak: Tri pusat pendidikan di Indonesia masih sulit dikembangkan, ditandai dengan kesulitan mengintegrasikan program pendidikan antara keluarga, sekolah dan masyarakat yang merupakan sebagai penanggungjawab pendidikan. Tujuan penelitian ini untuk memetakan dan menganalisis tripusat pendidikan dalam pengembangan pendidikan di Indonesia. Menggunakan metode kepustakaan atau studi pustaka, yang sumberdata diperoleh dari review tulisan-tulisan ilmiah, artikel-artikel ilmiah, buku-buku ilmiah baik online maupun cetak. Hasil penenlitian dapat disimpulkan tripusat pendidikan terdiri dari pendidikan keluarga, sekolah dan masyarakat. Pendidikan keluarga merupakan lembaga pendidikan pertama, karena orang tua yang senantiasa menyiapkan bekal pendidikan yang baik untuk anak-anaknya. Kemudian pendidikan sekolah merupakan anak mendapatkan pendidikan melalui lingkungan sekolah, manusia menerima pendidikan secara formal melalui materi pendidikanÂ  dan ekstrakulikuler dengan segala ketentuan dan struktur yang sudah diatur didalamnya, pendidikan formal di sekolah ini ditempuh selama sembilan tahun secara normalnya yang disusun melalui program SD, SMP, dan SMA. Sedangkan pendidikan masyarakat melalui lembaga-lembaga pendidikan non formal, seperti bimbingan belajar (bimbel), TPQ (Taman Pendidikan Quran), Organisasi dalam masyarakat (Remaja Islam Masjid), dan banyak lembaga pendidikan non formal lainnya yang ada dalam masyarakat. Dengan demikian dapat disarankan bahwa dalam upaya pengembangan pendidikan, maka tingkatkan peran fungsi dan tanggungjawab tripusat pendidikan di Indonesia.Kata Kunci: Tri Pusat Pendidikan, Pengembangan, Pendidikan Islam.